2016
DOI: 10.5433/1679-0359.2016v37n5supl2p3549
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for bovine tuberculosis in the State of Bahia, Brazil

Abstract: An epidemiological study was carried out in order to characterize the bovine tuberculosis situation and to support the planning and implementation of the National Program for the Control and Eradication of Bovine Tuberculosis in the State of Bahia, owing to the importance of the disease in causing economic burdens and its impact on public health. The State was divided into four regions. In each region, properties were randomly chosen and, a pre-established number of animals was also randomly selected; these an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
0
12

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 31 publications
8
47
0
12
Order By: Relevance
“…Studies based on bovine tuberculosis, conducted in 12 Federative Units, which contain 75% of the Brazilian herd, showed herd prevalence estimates between 0.5% and 9.0% in Santa Catarina and São Paulo, respectively (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016;GALVIS et al, 2016;GUEDES et al, 2016;LIMA et al, 2016;NÉSPOLI et al, 2016;QUEIROZ et al, 2016;ROCHA et al, 2016;SILVA et al, 2016;VELOSO et al, 2016;VENDRAME et al, 2016). The same authors observed that the risk of bovine tuberculosis increased in larger dairy cattle herds on farms that use some degree of automation in the dairy production process.…”
Section: Resultsmentioning
confidence: 51%
“…Studies based on bovine tuberculosis, conducted in 12 Federative Units, which contain 75% of the Brazilian herd, showed herd prevalence estimates between 0.5% and 9.0% in Santa Catarina and São Paulo, respectively (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016;GALVIS et al, 2016;GUEDES et al, 2016;LIMA et al, 2016;NÉSPOLI et al, 2016;QUEIROZ et al, 2016;ROCHA et al, 2016;SILVA et al, 2016;VELOSO et al, 2016;VENDRAME et al, 2016). The same authors observed that the risk of bovine tuberculosis increased in larger dairy cattle herds on farms that use some degree of automation in the dairy production process.…”
Section: Resultsmentioning
confidence: 51%
“…This prevalence of infected herds is equal to those observed in the states of Bahia, Paraná, Rio Grande do Sul, Mato Grosso, Rondônia, Goiás, Pernambuco, and Distrito Federal. It exceeds the prevalence of infected herds in the State of Santa Catarina and is lower than those observed in São Paulo, Minas Gerais, and Espírito Santo (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016;GALVIS et al, 2016;LIMA et al, 2016;NÉSPOLI et al, 2016;QUEIROZ et al, 2016;RIBEIRO et al, 2016;ROCHA et al, 2016;SILVA et al, 2016;BAUMGARTEN et al, 2016;VENDRAME et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Studies conducted on bovine tuberculosis in 12 Federative Units, which account for 66% of the Brazilian herd, showed prevalence of infected herds ranging from 0.36% in the Distrito Federal to 9.0% in São Paulo (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016;GALVIS et al, 2016;LIMA et al, 2016;NÉSPOLI et al, 2016;QUEIROZ et al, 2016;RIBEIRO et al, 2016;ROCHA et al, 2016;SILVA et al, 2016;BAUMGARTEN et al, 2016;VENDRAME et al, 2016 Azambuja (2010) found that 12% (24/200) of bovines tested positive for the intradermal comparative cervical tuberculin diagnostic test in the milk basin of Caarapó, a municipality located in the center of the Southern Plateau region of the State. In contrast, Piva Filho (2013), using the same diagnostic test, found a rate of positive-testing animals of 0.26% in the municipality of Parnaíba (MS).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of infected herds in these units varied between 0.36%, in the Federal District (Brasília), and 9.0%, in São Paulo (BAHIENSE et al, 2016;BARBIERI et al, 2016;DIAS et al, 2016;GALVIS et al, 2016;GUEDES et al, 2016;NÉSPOLI et al, 2016;QUEIROZ et al, 2016;RIBEIRO et al, 2016;ROCHA et al, 2016;SILVA et al, 2016;BAUMGARTEN et al, 2016;VENDRAME et al, 2016).…”
Section: Previous Studies Have Been Conducted In 12mentioning
confidence: 99%